Finger Number and Device Performance: A Case Study of Reduced Graphene Oxide Microsupercapacitors. Issue 2 (20th October 2020) - Li, Qi; Smith, Anderson D.; Vyas, Agin; Cornaglia, Fabio; Anderson, Alec; Haque, Mazharul; Lundgren, Per; Enoksson, Peter
Abstract : Microsupercapacitors (MSCs) are recognized as suitable energy storage devices for the internet of things (IoTs) applications. Herein is described the work conducted to assess the areal energy and power densities of MSCs with 2, 10, 20, and 40 interdigital finger electrodes on a fixed device footprint area (the finger interspacing is fixed at 40 μm, and the finger width and length are allowed to vary to fit the footprint area). The MSCs are based on reduced graphene oxide (rGO) materials and fabricated with a spin‐coating and etch method. The performance evaluation indicates a strong dependency of areal capacitance and energy density on the number of fingers, and the maximum (impedance match) power density is also influenced to a relatively large extent, whereas the average power density is not sensitive to the configuration parameters in the present evaluation settings (scan rate 20–200 mV s −1 and current density of 100 μA cm −2 ). For the rGO‐based devices, the equivalent distributed resistance may play an important role in determining the device resistance and power‐related performance. Abstract : The finger number influences significantly the areal energy and maximum power densities, whereas it has little impact on the average power density of the microsupercapacitors in the present case study, which are designed to a fixed device footprint area and finger interspacing, and based on reduced graphene oxide electrodes.